Upaya Meningkatkan Kemampuan Membaca Dengan Media Big Book pada Pembelajaran Bahasa Indonesia di Kelas 1 SDIT Ar-Ridha Desa Pantai Cermin - Hanum, Faridah (ALACRITY : Journal of Education, 2024)
This research aims to improve the reading ability of grade I elementary school students through the use of Big Book media. The approach used in this research is Classroom Action Research (PTK) with a cycle model consisting of four stages: planning, implementation, observation and reflection. The subjects of this research were first grade elementary school students who had difficulty recognizing letters, reading words and simple sentences. Big Book media was chosen because of its large size and attractive illustrations, which are expected to motivate students in the process of learning to read. The research results show that the use of the Big Book significantly increases students' reading interest and ability. This can be seen from the increase in students' reading test scores in each cycle. The use of the Big Book also encourages active involvement of students and makes it easier for them to understand reading. Based on these results, Big Book media is effectively used as a means of learning to read for grade I elementary school students.